An Infant With Medulloepithelioma Successfully Treated by High-dose Chemotherapy Followed by Autologous Peripheral Blood Stem Cell Transplantation Without Radiotherapy. Issue 6 (August 2015) - Hayase, Tomomi; Morimoto, Akira; Kawahara, Yuta; Yagi, Masaki; Kanai, Nobuyuki; Nobusawa, Sumito; Hirato, Junko; Gomi, Akira
Abstract : Medulloepithelioma of the central nervous system (CNS) is a rare primitive neuroectodermal tumor characterized by highly malignant behavior occurring in early childhood. Few cases have been reported and optimal management remains unknown. Here, we report a case of CNS medulloepithelioma successfully treated with high-dose chemotherapy (HDCTX) followed by autologous stem cell transplantation (auto-SCT) without radiotherapy. At the last follow-up, 3.0 years after onset, the patient was alive with no sign of relapse and normal development. To the best of our knowledge, this is the first reported case of long-term survival of CNS medulloepithelioma treated by HDCTX/auto-PBSCT without radiotherapy.